Type of Parenting as a Moderator of Stress and Youth Problems in Adolescents - Punia, Poonam; Chaudhary, Nikita (JOURNAL OF INDIAN EDUCATION, 2023)
This study was conducted to examine: (a) the effect of single parenting on the stress level and problems of adolescent students and (b) the relationship between stress and problems of adolescent students. A sample of 120 adolescents was taken by following multistage random sampling. Data was collected using the Youth Problem Inventory made by Dr M Verma and the Student Stress Scale by Dr Zaki Akhtar. Analysis has been done using statistical techniques like mean, t-test, correlation, regression, and ANOVA. The results found that the stress level in dual parenting adolescent students was significantly high compared to single parenting adolescent students. However, an insignificant difference was observed in the level of problems for both categories of adolescents. Further, family problems, social problems, personal problems, and oversensitivity have shown a moderate positive correlation with stress levels, while school or college problems have shown a small positive correlation with stress levels. Further, single parenting has been found to have a significant moderating effect on the relationship between family problems and the stress level of adolescent students. The study highlights the importance of spreading awareness among teachers, parents, and society about the problems of single parenting children and counselling single parents and their children.